1996
DOI: 10.1161/01.str.27.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor Reactivity and Pattern of Collateral Blood Flow in Severe Occlusive Carotid Artery Disease

Abstract: The presence of an ophthalmic artery pathway may provide the first evidence of disturbed vasomotor reactivity. The use of cerebral angiography to evaluate collateral pathways must be considered carefully since transcranial Doppler ultrasound is a reliable noninvasive alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 29 publications
3
77
0
2
Order By: Relevance
“…Previous studies have indicated that hemodynamic and metabolic changes are more severe in patients without primary collaterals than in patients with primary collaterals, 3,37 and that the presence of secondary collateral flow is associated with an impaired hemodynamic status. 38,39 In this study, we found that patients with leptomeningeal collaterals and an occlusion of the ICA had a lower CBF and a prolonged trailing edge in the frontal lobe. No differences were found in symptoms between patients with and without leptomeningeal flow.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies have indicated that hemodynamic and metabolic changes are more severe in patients without primary collaterals than in patients with primary collaterals, 3,37 and that the presence of secondary collateral flow is associated with an impaired hemodynamic status. 38,39 In this study, we found that patients with leptomeningeal collaterals and an occlusion of the ICA had a lower CBF and a prolonged trailing edge in the frontal lobe. No differences were found in symptoms between patients with and without leptomeningeal flow.…”
Section: Discussionmentioning
confidence: 47%
“…5 MR imaging (n ϭ 358 patients) and TCD (n ϭ 268 patients) were used according to 9 and 6 grading methods respectively, with no assessments of interobserver agreement being reported (Tables 4 and 5). 2,13,19,27,31,35,51,[74][75][76][77][78][79][80][81][82][83][84][85][86] A total of 8 publications compared noninvasive LMF assessments with MR imaging (n ϭ 5), CT (n ϭ 2), or TCD (n ϭ 1) with a reference standard by using DSA; in each, a different grading scale for the criterion standard was used. 13,19,27,31,[34][35][36]51 …”
Section: Medline Andmentioning
confidence: 99%
“…1 In chronic hypoperfusion due to severe carotid stenosis or occlusion, flow via leptomeningeal vessels can maintain cerebral blood flow when primary collateral flow (via the arterial segments of the circle of Willis) is insufficient. 2,3 Better LMF is associated with less infarct growth and better outcome following acute stroke, 4,5 while poor collateralization is associated with hemorrhage after IA thrombolysis. 6 Numerous studies, using several imaging modalities and grading methods, suggest that leptomeningeal collaterals confer a benefit in stroke.…”
mentioning
confidence: 99%
“…However, its role in cerebral collateralization is somewhat controversial [9][10][11][12][13][14][15][16][17][18]. The ophthalmic artery (OA) is traditionally regarded as an important source of cerebral blood supply in patients with ICA occlusion [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Anzola and colleagues suggested that this pathway, although important for the intraorbital structures, was probably of limited functional significance to the hemispheric blood supply [14]. Accordingly, others proposed an hierarchy in cerebral collateralization, relegating the OA as a collateral of last resort [15,16]. Hu and co-workers reported in a prospective 4-year follow-up study that asymptomatic patients with ≥75% carotid artery stenosis or occlusion and ROAF had an elevated risk of occurrence of ischemic event, in contrast to patients with forward OA flow [17].…”
Section: Introductionmentioning
confidence: 99%